Architectural User Interfaces: Themes, Trends and Directions in the Evolution of Architectural Design and Human Computer Interaction. (March 2013) - Dade-Robertson, Martyn
This paper reviews the historical and contemporary relationships between architectural design and Human Computer Interaction (hereafter HCI). Through this discussion the paper focuses on the enduring use of architecture as a metaphor in interaction design and the growing recognition that architectural space shapes the territory within which we interact with computational information. The paper begins with a brief discussion of the History of HCI before examining the relationship between the development of the computer Graphical User Interfaces (hereafter GUIs) and more recent work on Ubiquitous and Pervasive Computing. The paper then explores some current themes in HCI with a view to looking for potential overlaps between architectural design and new trends in the design of computational systems.